Een groot Nederlander: J.P.Ph. Clinge Fledderus (1870-1946) - Aalders, Maarten J. (Acta Neerlandica, 2020)
This article dives into a part of the life and personal history of J.P.Ph. Clinge Fledderus (1870-1946), consul of the Kingdom of the Netherlands, who played a crucial role in organizing relief for Hungary in the Interbellum and the organization of the possibilities for Hungarian children to recover from the effects of post-war famine and malaise after the First World War by giving them a holiday of some months in the Netherlands. A commemorative marble plaque for him still can be found on the front of the building at the Üllői út 4 in Budapest.